The Oregon Trail. Across the plains [videorecording (VHS)] - Boettcher, Steven J.; Trinklein, Michael J. (Films for the Humanities, 1993)
Follows the first leg of the journey along the Oregon Trail from Independence, Missouri to Fort Laramie, Wyoming. Discusses landmarks along the route, the problems of camping in the wilderness, and encounters with Native Americans.